Optimasi Impian Captain Tsubasa Bagi Persepakbolaan Jepang Spektrum Pendidikan Islam - Robingun Suyud El Syam; Bambang Sugiyanto (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this article is to reveal the optimization of Captain Tsubasa's dream for Japanese football on the spectrum of Islamic education, by unraveling how far the influence of the animated film Captain Tsubasa in whipping up the fighting spirit of the young generation of Japan, then contextualizing it in Islamic education, where problems have not been encountered before. This research is a qualitative descriptive, with the data collection technique using the polegulation, and analyzed inductively. Problems are analyzed with Max Weber's work ethic theory. The results of the study concluded: that Captain Tsubasa's dream in his animated film is able to be a motivator, especially for the young generation in Japan in terms of football so that in the future the National Team is able to win the Asian Cup and consistently participate in the World Cup. In the context of Islamic education, a Muslim must have a work ethic, namely a personality attitude that gives birth to a very deep belief that work is not only to glorify oneself, to show humanity, but as a form of manifestation of good deeds. This work ethic is well practiced in people's lives so that Muslims become strong as a community, so this research recommends that this work ethic be a way of life within the framework of nation and religion.